2011
DOI: 10.1073/pnas.1018862108
|View full text |Cite
|
Sign up to set email alerts
|

Comparative oncogenomics identifies breast tumors enriched in functional tumor-initiating cells

Abstract: The claudin-low subtype is a recently identified rare molecular subtype of human breast cancer that expresses low levels of tight and adherens junction genes and shows high expression of epithelial-to-mesenchymal transition (EMT) genes. These tumors are enriched in gene expression signatures derived from human tumorinitiating cells (TICs) and human mammary stem cells. Through crossspecies analysis, we discovered mouse mammary tumors that have similar gene expression characteristics as human claudin-low tumors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
252
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(268 citation statements)
references
References 45 publications
(52 reference statements)
14
252
2
Order By: Relevance
“…2, A, solid line, and B). IC 50 values for MS inhibition across the different cell lines is ϳ20 M, the same IC 50 value observed for inhibition of the cytokine-induced NFB pathway in adherent monolayer cultures.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…2, A, solid line, and B). IC 50 values for MS inhibition across the different cell lines is ϳ20 M, the same IC 50 value observed for inhibition of the cytokine-induced NFB pathway in adherent monolayer cultures.…”
Section: Resultsmentioning
confidence: 51%
“…All of these end points were attenuated by DMF or IKK7 to the same extent (Fig. 3, A and B), 50 values were calculated with GraphPad software using normalized data. G, DMF has no effect on estrogen receptor target gene TFF1 and IGFBP4 mRNA, measured in MCF-7 cells pretreated with DMF (20 M) for 2 h, followed by estrogen treatment (E2, 10 nM) for another 2 h. The different letters above bars indicate significant difference between treatments, p Ͻ 0.001. suggesting that DMF can abrogate MS formation by inhibiting the NFB pathway.…”
Section: Resultsmentioning
confidence: 99%
“…74,75 In agreement with this, molecular analysis of p53-null breast cancers classified them as having the claudin-low tumor gene signature, that is, cancers with dominant EMT and cancer stem cell characteristics. 76 In addition, TGFb directly regulates the majority of the EMT-TFs. 41 We found that TGFb, via Smad signaling, upregulates HMGA2 to drive EMT, 19 and this has been complemented independently in vivo as HMGA2 overexpression causes metastasis, 77 further reinstating the link between EMT and metastasis.…”
Section: Smad and Non-smad Signaling In Emtmentioning
confidence: 99%
“…RNA was hybridized to custom murine Agilent microarrays and normalized as described (Herschkowitz et al 2007(Herschkowitz et al , 2012. Data were deposited into the Gene Expression Omnibus (accession no.…”
Section: Microarray Expression Profilingmentioning
confidence: 99%